The Effectiveness of Peace Education Program on the Preschoolers’ Social Behaviour in the Sultanate of Oman - Rashid Al Mushaqiri, Mahfouda; Bin Ishak, Zahari; Muin Ismail, Wail (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2021)
Purpose – This research aims to measure the effects of the peace education program on the social and emotional behaviours of preschool children in the Sultanate of Oman. Children should be equipped with basic values, such as respecting the efforts and ideas of others, forming a comprehensive and positive relationship with people, possessing the skills of empathy, and resolving conflicts in peaceful ways.Design/methods/approach – The researcher adopted the quasi-experimental approach, and the current study presented the Peace Education Program (PEP) for children aged 4–6 years in the Sultanate of Oman. The participants consisted of 40 children in the experimental group and 40 children in the control group. The researcher used a scale with picture choice questions containing two pictures per question to measure the behaviours of children before and after the treatments. The peace education program for the study also included 28 training sessions that were presented for 15 weeks at a duration of one hour per session.Findings – The current study results also favoured the experimental group, as an improvement in their social behaviour was observed after joining the program.Research implications/limitations – The research demonstrates that peace is a key prerequisite for developing a balanced life, especially in childhood. The results may be of great significance in measuring and improving children's behaviour through (PEP).Practical implications – The study findings may likely be fruitful to Oman's pupils, educators, curriculum designers, and educational policy-makers.Originality/value – This study has been successful in focusing on some aspects of growth and behaviour enhancement in children. Paper type Research paper